The Role of Human Capital in Enhancing The Growth of Startup and Its Future Research Direction - Ar Rahim, Tiffany; Gustomo, Aurik; Freiburghaus, Teresa (AFEBI Management and Business Review, 2025)
In the era of innovation and digital transformation, startups have become vital contributors to economic development and technological progress. However, sustaining growth in high-risk and resource-constrained environments requires more than novel ideas; it necessitates strategic internal capabilities, particularly in human capital. This study aims to explore how human capital enables startups to achieve competitive advantage and organizational growth by applying the Resource-Based View (RBV) framework. Using a Systematic Literature Review (SLR) approach, this research identifies four main thematic clusters: (1) Founders’ and team human capital, (2) Talent acquisition and management, (3) Knowledge and intellectual resources, and (4) Innovation and capability development. The findings also reveal several mediators and moderators that influence the relationship between human capital and startup outcomes. The study observes an increasing scholarly focus on digital skills and collective knowledge, while identifying research gaps in longitudinal, resource-constrained, and emerging market settings. This review provides both scholars and practitioners with a comprehensive foundation for designing more effective human capital strategies in early-stage ventures.